Employee Training and The Adoption of E-Government in Local Governments in Uganda: A Case Study of Jinja Local Government - Mugavu, George; Mbabazi, Phelix Businge; Baremwire, Mary Bekoreire; Mucunguzi, Abel (Asian Journal of Social Science and Management Technology, 2025)
The purpose of this study was to establish the relationship between employee training and the adoption of e-government in Jinja local government. The study was guided by pragmatism as the research philosophy in which cross-sectional and case study research designs were embedded. The mixed research approach was employed with both quantitative and qualitative approaches given attention. As such, deductive and inductive research strategies were used. A total sample size of 200 respondents was drawn from a target population of 400 using Yamane (1967) formula for sample size determination. As such, stratified and purposive sampling techniques were mainly employed. This paper further provides detailed review of literature in tandem with the relationship between employee training and the adoption of e-government. The Pearson correlation results depicted was 0.509**. The P-value that was associated with this correlation was 0.000. The P-value of 0.000, was less than 0.01 which depicted that the observed correlation was statistically significant at 0.01 level. This correlation analysis depicted that there was a moderate positive statistically significant relationship between employee training and the adoption of E-government in Jinja local government. These findings thus implied that there was need for officials in the local government to continuously strengthen the training function in the area of information communication technologies (ICTs) in order to ensure the effective adoption of E government in Jinja District local government since training was revealed to have a significant moderate positive relationship with the adoption of E-government in Jinja Local government. We concluded that Employee Training significantly affected the adoption of e-government in Jinja local government ; The researchers vehemently recommended the need for continuous training of the Jinja District Local government staff in computer hardware and software as these would improve on their skills in those areas which would be very critical in helping the staff to undertake the E-government adoption tasks easily and also contribute to a positive attitude towards electronic work among the staff in Local governments in Uganda, the researchers further recommended the need for local government top officials to always consult with, and involve all the relevant the staff of the local governments on how ICTs hardware and software trainings would be conducted and as would always ensure fruitful trainings which would propel ensure efficiency and effectiveness among staff in using the e-government plat forms in Local Governments in Uganda.